Researching accounting: self-reconstruction and communication in early research settings - Mustafa, Hasri (Emerald, 2018)
Purpose: The purpose of this paper is to engage, cooperate and communicate for a more visible form of research accounting in early research settings, especially by those in non-native English speaking and developing nations. Design/methodology/approach: The paper highlights four early research settings: in writing a research undertaking, in gaining acceptance of a research undertaking, in situating the self in the research context and in the renegotiation of the research context. Findings: The paper finds that although organisations offer a forum for a discussion of socialising form of accounting, organisational communication inverts many of the norms of academic etiquettes. It interrupts, takes statements out of context and challenges the academic claim of accounting as a language of business. Practical implications: The paper alerts corporations, managers, supervisors and researchers that communicating accounting is distinct from communication skills, though both emphasise that communications comprise behaviours which can be learned. Inexperienced researchers are not the only potential readers of the paper. The study is an attempt to provide accounting researchers with a resource for making informed decisions concerning the communication type they face and by placing their research agenda within the appropriate accounting characterisations. Originality/value: The paper broadens the view of what constitutes knowledge of accounting and the knowledge about accounting and the ways to attain them. The key topics explored in the study provide “hands-on” methodological issues that could be adapted for use on similar programmes.